D’un antipode à l’autre, trajectoire de trois sculptures architecturales kanak - Marie Adamski (Les Cahiers de l'École du Louvre)
This article traces the provenance and fate of three elements of Kanak architecture collected by Pastor Rey Lescure in 1931–32 on the east coast of New Caledonia for the Musée d’Ethnographie du Trocadéro (MET) at the request of Paul Rivet and Georges-Henri Rivière, then head of the museum. They acquired the status of “witness objects” before the head of the Oceanic collection, Charles van den Broek, decided to use them as bargaining chips in 1938–39, when the MET became the Musée de l’Homme. He came to an agreement with Serge Brignoni, a Swiss surrealist artist living in Paris, giving them and another sculpture to him in exchange for six Melanesian objects. The Kanak sculptures, which interested their new owner above all for their aesthetic value, became part of a major collection of art nègre. Now in the Museo delle Culture Extraeuropee, which houses the artist’s collection in Lugano, Switzerland, they have finally found a museum setting. Through the singular biography of these objects, we will analyse the changing status of the works and the different interests they arouse over time, from their creation in New Caledonia to their exhibition in Lugano, via Paris.